Cover Image. Issue 1 (8th February 2022) - Qi, Jiaqian; Lv, Xin; Chen, Jia; Wang, Hong; Chu, Tiantian; Tang, Yaqiong; Pan, Tingting; Zhou, Meng; Cai, Chengsen; Ren, Yuan; Liu, Yuejun; Fan, Yi; et al.
Abstract : The cover image is based on the Original Article TNF‐α increases the risk of bleeding in patients after CAR T‐cell therapy: A bleeding model based on a real‐world study of Chinese CAR T Working Party by Jiaqian Qi et al., https://doi.org/10.1002/hon.2931 .